Rethinking Politics From China Through Relationality And Moral Leadership A Conceptual Analysis: RETHINKING POLITICS FROM CHINA THROUGH RELATIONALITY AND MORAL LEADERSHIP A CONCEPTUAL ANALYSIS - Dhani, Muhammad Dhani; Pramono, Sugiarto (Kajian Hubungan Internasional, 2025)
The dominance of Western theories in the study of International Relations (IR) has long shaped the ontological, epistemological, and normative assumptions of the discipline. With the rise of China as a global actor, intellectual efforts have emerged to develop IR theories grounded in China’s historical experience and philosophical traditions. This article examines the conceptual foundations, historical development, and major contributions of Chinese International Relations theory to the enrichment of global IR theory. Focusing on Qin Yaqing’s relational approach and Yan Xuetong’s moral realism, the article demonstrates that Chinese IR theory offers a substantive critique of individualism, instrumental rationality, and material reductionism embedded in Western IR theories. By emphasizing social relations, morality, and ethical leadership, Chinese IR theory broadens prevailing understandings of power, legitimacy, and international order. Drawing on Amitav Acharya’s Global IR framework and Hun Joon Kim’s analysis of IR theory with Chinese characteristics, the article argues that the contribution of Chinese IR theory lies not in claims of cultural superiority, but in its capacity to enrich theoretical pluralism and to decolonize IR knowledge. It concludes that Chinese IR theory has the potential to become an integral component of Global IR, provided that it is developed in a critical, dialogical, and context-transcending manner.